The Denial of Antiblackness : Multiracial Redemption and Black Suffering - Vargas, João Helion Costa (Book collections on Project MUSE., 2018)
"João H. Costa Vargas examines how antiblackness affects society as a whole through analyses of recent protests against police killings of black individuals in both the United States and Brazil, as well as the everyday dynamics of incarceration, residential segregation, and poverty. With multisite ethnography ranging from a juvenile prison in Austin, Texas, to grassroots organizing in Los Angeles to Black social movements in Brazil, Vargas finds the common factors that have perpetuated antiblackness, regardless of context. Ultimately, he asks why the denial of antiblackness persists, whom this narrative serves, and what political realities in makes possible."--Page 4 of cover.